2004
DOI: 10.1097/01.tp.0000101822.50960.ab
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus and mycophenolate mofetil are potent inhibitors of fibroblast proliferation after lung transplantation1

Abstract: RAD and MMF were the most potent antifibroproliferative drugs and were effective at concentrations achieved clinically, supporting their use for the treatment of patients with early BO. Our method holds promise as an in vitro model to assess the likely in vivo responses of human lung fibroblasts to specific immunosuppressive drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 29 publications
4
61
0
3
Order By: Relevance
“…For this reason, the lack of success of current treatments for OB in lung transplantation is not surprising, given that they focus on the suppression of alloreactive cells, of which there are few in the OB lesion. In fact, very few studies have examined fibroblast proliferation in response to currently used immunosuppressant transplant medications (32,33). Studies testing these agents on myofibroblast transdifferentiation and proliferation, particularly, Smad3 and MAPK signaling, may be even more appropriate as these cells have a phenotype clearly distinct from that of undifferentiated fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the lack of success of current treatments for OB in lung transplantation is not surprising, given that they focus on the suppression of alloreactive cells, of which there are few in the OB lesion. In fact, very few studies have examined fibroblast proliferation in response to currently used immunosuppressant transplant medications (32,33). Studies testing these agents on myofibroblast transdifferentiation and proliferation, particularly, Smad3 and MAPK signaling, may be even more appropriate as these cells have a phenotype clearly distinct from that of undifferentiated fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Everolimus has been reported to induce a cell cycle arrest at the G 1 phase by blocking mTOR activity (Schuler et al, 1997;Azzola et al, 2004), but the effect of the association with fluvastatin has not been studied. We therefore investigated the effect of everolimus alone and in combination with fluvastatin on cell cycle progression using two different approaches: [ 3 H]thymidine incorporation assay and flow cytometry analysis of the cell cycle.…”
Section: The Synergistic Effect Of Combination Everolimusmentioning
confidence: 99%
“…In contrast to the report by Morizane et al [65], we used an immunosuppressive agent, namely, tacrolimus, at 0.05 mg/kg/day with subcutaneous injection. This dose is lower than the maintenance dose used for human organ transplantation [66][67][68]. Our results revealed that numerous grafted ESC-NS/PCs survived in the presence of a lowdose of tacrolimus after SCI.…”
Section: Discussionmentioning
confidence: 87%